"Assassin's Creed reminds us that history is human experience": Students' senses of empathy while playing a narrative video game. (2nd January 2019) - Gilbert, Lisa
ABSTRACT: Research into students' interactions with historical video games is limited and tends to focus on teacher mediation. As a result, little is known about the meanings that students independently construct as they consume this form of media. This qualitative interview study uses Assassin's Creed, a narrative video game with a historical setting, as a site of inquiry. Students described a sense of immediate access to history that contrasted with school-based learning, a sense of human connection to people in the past, and increased perception of multiple perspectives in history. They also evidenced a willingness to allow the games to rewrite their beliefs about history, and theorized about the games' historical accuracy. However, students tended to miss opportunities for critical engagement with this visceral sense of immersive experience. As such, implications are raised regarding ways to promote critical investigation into gameplay experiences as well as the importance of fostering a sense of human connection to history through social education.